Labyrinthine Fistula in Cholesteatoma Patients: Outcomes of Partial Labyrinthectomy With “Underwater Technique” to Preserve Hearing - Pace, Annalisa; Milani, Alessandro; Messineo, Daniela; Rossetti, Valeria; Cocuzza, Salvatore; Maniaci, Antonino; Vicini, Claudio; Iannella, Giannicola; Magliulo, Giuseppe (Frontiers in Neurology, 2022)
Labyrinthine fistula (LF) is one of the most important complications of cholesteatoma and is defined as an abnormal communication between the inner and the middle ear. The aim of this study is to describe our experience with partial labyrinthectomy evaluating the postoperative hearing results. Twenty-one patients who presented labyrinthine fistula in the semicircular canals were included in the present study. Hearing impairment was present in 48% of patients (10/21). Pre-operative assessment using the Gardner- Robertson hearing classification showed: 52% Class I; 48% Class II. Post-surgical Gardner- Robertson hearing classification evidenced: 43% Class I; 57% Class II. The presence of LF is usually considered a negative prognostic factor for hearing preservation. The key point of partial labyrinthectomy surgery is the preservation of structures, keeping them wet with Ringer’s solution throughout the procedures, and not performing suction close to the opened LF. The bony labyrinth is drilled underwater without suction, removing the entire cholesteatoma matrix and quickly plugging the site before and after the LF. This faster plugging of the labyrinth makes it possible to preserve the peri-lymph and endo-lymph fluid and hearing function. This study showed that partial labyrinthectomy is useful for maintaining serviceable hearing in patients with LF.